High genetic connectivity among pink shrimp Farfantepenaeus paulensis (Pérez-Farfante, 1967) groups along the south-southeastern coast of Brazil - Teodoro, S. S.A. [UNESP]; da Silva Cortinhas, M. C.; Proietti, M. C.; Costa, R. C. [UNESP]; Dumont, L. F.C. (Elsevier, 2020)
The pink shrimp Farfantepenaeus paulensis is one of the most important fishing resources along the south-southeast coast of Brazil. Its fishing zone includes two main reproductive stocks, located at the coasts of Santa Catarina and São Paulo states. The species life cycle includes an offshore reproductive stage and juvenile recruitment to estuarine areas; therefore, adults are caught in oceanic areas by industrial fisheries and juveniles in estuarine areas by artisanal fisheries. The unrestricted growth of the industrial fleet, along with the increase of artisanal fishing in estuarine areas and the low effectiveness of fishery legislation, led to a collapse of the pink shrimp fishery in the late 1990s. The present work aimed to assess the population genetics of the pink shrimp F. paulensis throughout its main distribution in the Southwestern Atlantic (SWA), to verify whether different fishing stocks also represent different genetic stocks. Based on the evaluation of the mtDNA control region (D-loop), we detected high connectivity and absence of genetic structure among F. paulensis groups in the SWA. Fixation indexes, Analysis of Molecular Variance and a haplotype network also showed no significant genetic differences, with individuals sharing haplotypes among more than one region. Mismatch analysis showed unimodal distributions for all the sampled populations with high haplotype diversity and low nucleotide diversity, showing a pattern of recent demographic expansion, which was corroborated by the Tajima's D and Fu's Fs neutrality tests. Estimates of migration rates indicated high gene flow, with a large number of migrants exchanged between regions. All obtained results are consistent with a panmitic population of F. paulensis. This scenario is a result of a complex interaction of several factors, from the influence of currents on larval dispersal to the effect of overfishing. The knowledge on the diversity and genetic structure of F. paulensis is a fundamental part of the scientific basis necessary for decision makers to elaborate adequate management strategies for pink shrimp stocks.
Keywords: Demographic analysis; Genetic diversity; Genetic monitoring; mtDNA control region (D-loop); Population connectivity